2021
DOI: 10.3329/jbcps.v39i3.54163
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Nurses Regarding Essential Newborn Care in Special Care Neonatal Units (SCANU) of Different Hospitals of Chattogram, Bangladesh

Abstract: Background: The advancements in intensive care in recent decades have enabled better survival of newborn. Knowledge of essential newborn care is important for the survival, growth, and development of a newborn. In spite of its essentiality, most health-care professionals do not know and follow the World Health Organization recommendation. Aim and objectives: The aim of this study was to assess the knowledge of nurses regarding essential newborn Care in Special Care Neonatal Units (SCANU). Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
2
1
1
Order By: Relevance
“…The study results revealed that most nurses had good knowledge of essential newborn care, consistent with a study by Ayiasi et al, 2014 [15], which showed that most nurses had good knowledge about ENC management and identifying/stabilizing LBW babies. In addition, 56.0 % of nurses were attending special courses/training in neonatology in T Sharmin et al (2021) [8], in contrast to our study, where only 18 % have done special courses in neonatology.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The study results revealed that most nurses had good knowledge of essential newborn care, consistent with a study by Ayiasi et al, 2014 [15], which showed that most nurses had good knowledge about ENC management and identifying/stabilizing LBW babies. In addition, 56.0 % of nurses were attending special courses/training in neonatology in T Sharmin et al (2021) [8], in contrast to our study, where only 18 % have done special courses in neonatology.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, 48 % of nurses were Muslim, and 46 % of nurses were married, similar to T Sharmin et al (2021) [8]. In our study, 78 % of the nurses had done BSc nursing 22 % had diplomas.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations